The Influence of Tourist Attraction, Destination Image and Accessibility on Interest in Visiting Tourist Objects - Salmah Salmah; As'at Rizal (Indonesian Journal of Cultural and Community Development, 2022)
The purpose of this study was to determine the effect of tourist attractiveness, destination image and accessibility on the interest in visiting the Bima Snake Island tourism. This research is a descriptive study using quantitative methods. The data collection technique is by distributing questionnaires to 100 respondents. The analysis technique used in this research is multiple linear regression, F test, t test, multiple correlation coefficient (R) test, and multiple determinant coefficient (R²) using the SPSS (Statistical Program For Social Science) version 18.0 for Windows. The results of this study were obtained based on the validity test of a valid questionnaire statement. It shows that the variable of tourist attractiveness affects visiting interest, the variable of destination image influences visiting interest, accessibility influences visiting interest, and variables of tourist attraction, destination image, accessibility simultaneously influence the interest in visiting the tourist interest of the snake island of Bima NTB.